Model Bangkitan dan Tarikan Pergerakan, di Jalan Veteran Lamongan Karena Perkembangan Kampus Unisla - Afif, Naufal; Gardjito, Edy (Jurnal Talenta Sipil, 2024)
Unisla has experienced an increase in the number of lecturers and students successively from year to year. In addition, lecture buildings and educational facilities also continue to improve over time. The purpose of this study is to determine the model of attraction and generation of movement in the Unisla campus area, and to determine the factors that influence the attraction and generation of movement that will occur due to the development of the Unisla campus. The method in this study uses the method of regression analysis, slovin and SPSS. Based on the analysis, the results of the generation model and the attraction of movement in the Unisla campus area can be explained by the equation Y = 556.448 + -0.963X, with an R2 value close to one of 0.593, indicating a good fit between the model and the data. The factor that has a significant influence on the generation and attraction of movement in the Unisla campus area is the mode of transportation chosen by the subject. Motorcycles have an effect of 90.26% on motion generation, whereas in terms of movement attraction, motorcycles also have an influence of 91.91%. In this case it can be interpreted that what has a big influence on the generation and attraction of movement in the Unisla campus area is motorbikes.